A Survey of Transfer Learning for Convolutional Neural Networks - Ribani, Ricardo; Marengoni, Mauricio (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and Images, 2019)
In this tutorial, we propose to show the advantages of using transfer learning in real-world problems. Transfer learning is an emerging topic that may drive the success of machine learning in research and industry. The lack of data on specific tasks is one of the main reasons to use transfer learning since collect and label data can be very expensive and can take time. There are also recent concerns with privacy which makes difficult to use real data from users. The use of transfer learning also helps to fast prototype new models when using pre-trained models in other datasets, since training on millions of images can take days or weeks and requires expensive GPUs. We’ll give an explanation about transfer learning, covering types of transfer learning, when and how to transfer knowledge. The tutorial will also cover a practical demonstration of different use cases using transfer learning, comparing results and explaining the advantages of using it or not.